Predatory competence of Danio rerio (Cypriniformes: Cyprinidae) and Poecilia reticulata (Cyprinodontiformes: Poeciliidae) as biocontrol agent of Aedes larvae (Diptera: Culicidae) under the laboratory condition (Bangladesh Journal of Zoology, 2024)
Predatory potential of Zebrafish, Danio rerio (Cypriniformes: Cyprinidae) and Guppy, Poecilia reticulata (Cyprinodontiformes: Poeciliidae) were evaluated to control Aedes mosquito larvae and thereby manage dengue epidemics in a sustainable, and eco-friendly manner. Under laboratory conditions, size-matched fish of each species were introduced into separate plastic containers containing 2 liters of tap water and 100 third instar larvae of Aedes. In addition, different prey combinations were used to assess the comparative predation potential of the fishes. Mosquito prey preferences were assessed using Manly’s preference index. Over 24-hours of laboratory conditions, a significant difference (p